Fiscal crises in US cities: Structural and non-structural causes - Guntram B. Wolff (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
Financial difficulties of U.S. cities have recently become a major issue of concern. However, there is little agreement on why certain cities experience crises while others do not. Two arguments are put forward: Cities suffer from (1) structural problems like high immigration, congestion etc. (2) nonstructural political problems like the weakness of the mayor, union-power etc. Starting from a common pool model of municipal goods we estimate demand equations for spending and debt with structural variables. The estimation is based on 900 US cities in 1985, 1991 and 1999. Structural factors predicted by the model explain most of the variation of spending and debt levels. Furthermore coefficients are stable over time. However, excessively high debt burdens as indicators of potential crisis, and high spending levels are outliers and not explained by structural factors.
Keywords: 330